The Preclinical Evaluation of a Second-Generation Antivenom for Treating Snake Envenoming in India - Saurabh Attarde; Ashwin Iyer; Suyog Khochare; Umesh Shaligram; Mayur Vikharankar; Kartik Sunagar (Toxins, 2022)
Snake envenoming afflicts the Indian subcontinent with the highest rates of mortality (47,000) and morbidity globally. The only effective treatment for snakebites is the administration of antivenom, which is produced by the hyperimmunisation of equines. Commercial Indian antivenoms, however, have been shown to exhibit a poor preclinical performance in neutralising venom, as a result of inter- and intrapopulation snake venom variation. Additionally, their poor dose effectiveness necessitates the administration of larger volumes of antivenom for treatment, leading to several harmful side effects in snakebite victims, including serum sickness and fatal anaphylaxis. In this study, we employed chromatographic purification to enhance the dose efficacy of commercial Indian antivenoms. The efficacy of this ‘second-generation’ antivenom was comparatively evaluated against six other marketed antivenoms using a number of in vitro and in vivo preclinical assays, which revealed its superior venom recognition capability. Enhanced purity also resulted in significant improvements in dose effectiveness, as the ‘second-generation’ antivenom exhibited a 3 to 4.5 times increased venom neutralisation potential. Furthermore, preclinical assays revealed the increased effectiveness of the ‘second-generation’ antivenom in countering morbid effects inflicted by the ‘big four’ Indian snakes. Thus, we demonstrate the role of simpler purification steps in significantly enhancing the effectiveness of snakebite therapy in regions that are most affected by snakebites.